Diversity of Endophytic Fungi from Red Ginger (Zingiber officinale Rosc.) Plant and Their Inhibitory Effect to Fusarium oxysporum Plant Pathogenic Fungi - ROHANI CINTA BADIA GINTING; NAMPIAH SUKARNO; UTUT WIDYASTUTI; LATIFAH KOSIM DARUSMAN; SIHEGIKO KANAYA (HAYATI Journal of Biosciences, 2013)
Indonesia has been known as a country with high medicinal plant diversity. One of the most common medicinal plant from Indonesia is red ginger (Zingiber officinale Rosc.). Nevertheless, limited studies of endophytic fungi associated with these medicinal plants are hitherto available. The objectives of this research were to study the diversity of endophytic fungi on red ginger and to analyze their potential as a source of antifungal agent. All parts of plant organs such as leaf, rhizome, root, and stem were subjected for isolation. Fungal identification was carried out by using a combination of morphological characteristic and molecular analysis of DNA sequence generated from ITS rDNA region. Thirty endophytic fungi were successfully isolated from leaf, rhizome, root, and stem of red ginger plant. Antagonistic activity was tested against Fusarium oxysporum, a pathogenic fungus on plants, using an antagonistic assay. Based on this approach, the fungi were assigned as Acremonium macroclavatum, Beltraniella sp., Cochliobolus geniculatus and its anamorphic stage Curvularia affinis, Fusarium solani, Glomerella cingulata, and its anamorphic stage Colletotrichum gloeosporoides, Lecanicillium kalimantanense, Myrothecium verrucaria, Neonectria punicea, Periconia macrospinosa, Rhizopycnis vagum, and Talaromyces assiutensis. R. vagum was found specifically on root whereas C. affinis, L. kalimantanense, and M. verrucaria were found on stem of red ginger plant.  A. macroclavatum was found specifically in red ginger plant’s organ which located under the ground, whereas C. affinis was found from shoot or organ which located above the ground. The antagonistic activity of isolated endophytic fungi against F. oxysporum varied with the inhibition value range from 1.4 to 68.8%. C. affinis (JMbt7), F. solani (JMd14), and G. cingulata (JMr2) had significantly high antagonistic activity with the value above 65%; and R. vagum (JMa4) and C. geniculatus (JMbt9) had significantly low antagonistic activity with the range value 0-10%.